(untitled) (Sound Stage Screen, 2025)
In speculating on how an infant human emerges into consciousness, William James deployed the active acoustic and haptic metaphor of a buzzing confusion, resonating in a sensing body. Resonance enters us as music, sound, acousma, timbre, and even subaural inputs. Per Veit Erlmann, resonance opens us to different ways of listening and being and thinking in a world of oscillating matter. As Erlmann chronicles, the body’s equipment (eye and ear, but also soul and viscera) have a history – most pointedly, the moment in which they were understood to be capable of sympathetic vibrations. Thus, by the time of James, the resonating subject is one posited by science as possessing strings and hairs, hammers and drums, rods and cones – all of which resonate with various energies coming from the world. Still, despite the fact that much of the physics of sound developed around water experiments, those studying how the human body captured those resonant properties ignored all the fluids in human bodies (notably, different fluid densities deployed by the basilar membrane in the inner ear). The Helmholtzian “piano key” approach dominated how music and sound were understood well up until the mid-20th century. To understand resonance viscerally, we would need Pauline Oliveros to compose music from the unpitched, uncoordinated, but moistly vocalizing co-resonating humans (Teach Yourself to Fly,1970). We would need Max Neuhaus to appeal to our fluid interfaces by resonating us under water (Water Whistle, 1971). And emergently, we might want Jana Winderen reminding us that creaturely resonances vibrate in frequencies and places we need our techno-prostheses to access (Aquaculture, 2010; Planktonium 2024).